LEGAL RECONSTRUCTION OF REGULATIONS MARRIAGE DIFFERENT RELIGIONS IN INDONESIA - Septiandani, Dian -; Soegianto, Soegianto -; Sukmadewi, Yudhitia Dyah; Susilo, Adhi Budi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to find the proper legal reconstruction regarding interfaith marriages in Indonesia. Article 2, paragraph (1) of the Marriage Law states that marriage is valid if performed according to the laws of each religion and BeliefBeliefBelief. Meanwhile, the content of the explanation of Article 35 of the Population Administration Law allows interfaith marriages. With this, the legal rules regarding interfaith marriages need to be reconstructed clearly and firmly so that there is the same understanding and implementation in the community because it will cause legal uncertainty. This research is a normative legal research with a statutory approach. The method of collecting secondary data is done through a literature study. The data obtained is analyzed qualitatively. The results of this study indicate that the regulation of marriage in Indonesia does not recognize the existence of interfaith marriages; it relies on the laws of each religion, so marriage marriage becomes invalid. The consequences impact the status of children as illegitimate or outside of marriage and the status of inheritance. Furthermore, related to the regulation of interfaith marriages, there is disharmony in the rules of the Marriage Law and the Population Administration Law; the provisions of Articles 35 and 36 of the Population Administration Law should be revoked because they cause a conflict of norms with the Marriage Law. This will provide legal certainty to the community.